Efektivitas Model Pembelajaran Think Pair Square Talkball Share Terhadap hasil Belajar Matematika - Nurhidayah Nurhidayah; Karmila Karmila; Nur Rahma (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2017)
This study aims to describe the effectiveness of mathematics learning outcomes through the learning model of think pair square talkball share on mathematics learning outcomes of students. The population in this research is the students of class VIII, with two classes as research sample that is class VIIIB and class VIIIA. Class VIIIB as an experimental class and class VIIIA as control class. The result of descriptive statistic analysis shows that the resultantness of learning result in the students of class VIIIB SMP Negeri 2 Sumarorong 90,32% complete and 9,67% not complete mean indicator of learning result of learners fulfilled. Observation results during the research, all students active in learning relationships and functions, as well as the response of learners included in the positive category. After the implementation of learning model think pair square talkball share then the result of learning mathematics achieved by students of class VIII SMP Negeri 2 Sumarorong experienced a significant increase, then the results of inferential analysis at a significant level a = 0.05 indicates that the use of learning model think pair square talkball share Effective in improving learning outcomes Mathematics in class VIII students SMP Negeri 2 Sumarorong.